New business models in broadcast television: the Netflix case - Heredia Ruiz, Verónica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2018)
Netflix, a platform with more than 100 million users in the world, has forever changed the way television is produced and consumed. This article analyzes how this new television model convergent with Internet has transformed the concept of programming and teleclairvoyance through intensified viewing or binge watching. A conceptual review identifies the main theoretical displacements on television, programming and audiences generated by the platform, as well as a documentary analysis of news articles on the subject, and the visualization of the Original contents published until May 2017.